Unstable angina following anaphylaxis. Issue 998 (6th February 2009) - Ameratunga, R; Webster, M; Patel, H
Abstract : A 55-year-old woman developed unstable angina following an episode of severe anaphylaxis which was treated with 0.5 mg intramuscular epinephrine (adrenaline). The exact cause of her ongoing unstable angina was uncertain but may have reflected either vasospasm superimposed upon an area of atherosclerotic coronary disease, or vasospasm induced plaque rupture. Four weeks later, she had a second episode of anaphylaxis, and suffered a cardiac arrest after receiving a bolus of intravenous epinephrine. This case illustrates the importance of careful assessment of patients after anaphylaxis, both to prevent recurrence and to treat complications from the episode. It highlights the dangers of intravenous epinephrine in treating anaphylaxis outside anaesthetic and intensively monitored settings.